Broadening brand engagement within the service-centric perspective: An intersubjective hermeneutic framework. Issue 2 (13th March 2017) - Seo, Yuri; Kelleher, Carol; Brodie, Roderick J.
Abstract : Purpose: While extant service-centric research has largely focussed on managerial advantages, few studies have addressed how brand engagement emerges in the broader context of consumer lives. The purpose of this paper is to develop a novel intersubjective hermeneutic framework that bridges the socially constructed as well as the individualised meanings of brand engagement in the context of service research. Design/methodology/approach: This conceptual paper adopts a theory-building approach based on recent developments in the service-centric marketing literature. Findings: The authors offer a novel theoretical perspective that recognises the intersubjective and phenomenological nature of individual and collective consumer brand experiences, and show how such experiences emerge from socially constructed brand engagement practices using the co-constituting lens of value-in-use. Research limitations/implications: The proposed conceptual framework invites further empirical and contextual investigations of intersubjective brand engagement in both online and offline contexts. Originality/value: The contribution of this framework is twofold. First, the authors draw on the intersubjective orientation and hermeneutic framework to provide conceptual clarity in relation to the nature of brand engagement practices, brand experiences, and value-in-use, and discuss their interrelationships. Second, the authors address the nature of meaning ascribed to engagement beyond customer-firm-brand relationships, and discuss why any given consumer's experience of brand engagement reflects a complex dialectic between socially constructed and individualised brand meanings. In doing so, the integrative framework recognises the interplay between the intersubjective and phenomenological natures of consumer brand experiences, and offers insights as to how these experiences are framed by broader socially constructed engagement practices.